Combined test of serum CgA and NSE improved the power of prognosis prediction of NF-pNETs. Issue 1 (January 2018) - Lv, Yang; Han, Xu; Zhang, Chunyan; Fang, Yuan; Pu, Ning; Ji, Yuan; Wang, Dansong; Xuefeng, Xu; Lou, Wenhui
Abstract : Purpose: Chromogranin A (CgA) and neuron-specific enolase (NSE) are important markers for neuroendocrine tumors; however, the clinical value of combining these markers has not been well studied. In this study, we investigated the utility of each marker individually and in combination for patients with nonfunctional pancreatic neuroendocrine tumors (NF-pNETs). Patients and Methods: In this study, NF-pNET patients and controls were recruited from December 2011 to March 2016; 784 serum samples from peripheral vein were collected. The clinical characteristics and biomarker values of all the individuals were recorded and analyzed. Tumor burdens were calculated by CT/MRI scan. Receiver-operating characteristic curves were constructed to assess the diagnostic predictive values; sensitivity and specificity were calculated to determine the cut-off value. Therapeutic responses reflected on the changes of the biomarkers' concentration were assessed by the RECIST criterion. Clinical relations between the prognosis and the biomarker values were also analyzed. Statistical significance was defined as P value less than 0.05. Results: Among the 167 NF-pNETs patients, 82 were males (49.1%) and the mean age was 50.0 (17.4). The mean CgA values of G1, G2 and G3 NF-pNENs were 75, 121 and 134 μg/L ( P  < 0.05), respectively. In NF-pNETs, CgA correlated with the WHO tumor grade (WHO G1 vs G2, P  < 0.05); the linear regression relationships were found between the tumor burdens (both in pancreas and liver) and CgA concentration ( P  < 0.001); changes in CgA and NSE concentrations also reflect treatment response ( P  < 0.001). Conclusion: CgA and NSE are important diagnostic and follow-up markers in patients with NF-pNETs. The combined monitoring of CgA and NSE possesses more accuracy than individual values of CgA and NSE at predicting prognosis and disease progression.